Service Competency Development System on People Management Work collaboratively with others and Emotional Intelligence of First-line Supervisors for High Value Tourist in Hotel Industry in the EEC - Anantanond, Sanon; Udompon, Wannapa; Tubsree, Chalong (Arts of Management Journal, 2024)
This research aims to: 1. Develop a system to enhance the service capacity in human resource management, teamwork, and emotional intelligence for first-line managers in the hotel industry to cater to high-income tourists in the Eastern Economic Corridor (EEC). 2. Evaluate the effectiveness of the developed system. The researchers employ a research and development (R&D) approach, utilizing the ADDIE model consisting of five phases: analyze, design, develop, implement, and evaluate. The researchers collected both qualitative and quantitative data for the study. A qualitative research method, including in-depth interviews and focus group discussions with first- and middle-level managers from hotels affiliated with the Eastern Thailand Hotel Association, was employed to collect data. The research results informed the creation of a workshop training course on “Managing Emotional Intelligence in Service and Teamwork for First-Line Managers,” lasting 12 hours and covering four topics: 1. Emotion Management and Positive Psychology; 2. Effective Communication and Teamwork; 3. Leadership, Personal Branding, and Presentation Skills in Service; and 4. Resilience and Change Management. The evaluation results of the developed system indicated that participants' post-training scores improved significantly, and their satisfaction ratings for the course were exceptionally high across all topics.